Mechanical and durability performance of textile reinforced cementitious composite panels - Daskiran, Mehmet Mustafa; Daskiran, Esma Gizem; Gencoglu, Mustafa (Elsevier BV, 2020)
Abstract Textile reinforced cementitious composites (TRCC) consist of technical textile and matrix material. A potential use of these new composite materials involves panels used as both a facade and strengthening material. As the use of these materials becomes widespread, the determination of their strength and durability properties becomes vital. In this study, textile reinforced cementitious composite panels were prepared by using a newly developed PPR (Pull pour roll) technique and machine. A polymer modified cementitious mortar was designed as matrix material and different textile materials were selected for the production of composite panels. Mineral admixtures, defoamer and superplasticizer materials were also used in the matrix mixture to obtain desired workability and mechanical properties. The influence of three different textile materials (Alkali Resistant Glass, Basalt and Polyvinylalcohol (PVA)) and the number of textile layers on the performance of composite panels were comparatively investigated. To simulate the outdoor environment composite panels will be exposed, wetting–drying curing regime was applied. Pull-off tests were carried out on composite panels before and after wetting–drying curing. In addition, diagonal compression tests were performed on infill walls strengthened with panels applied to one or double faces. Contribution of composite panels bonded to infill walls was investigated in terms of shear strength, shear modulus, ductility under shear and failure modes. Comprehensive experimental studies have shown that there is great potential for use of textile reinforced composite panels in the strengthening of infill walls.